The complete mitochondrial genome of Chlorotettix nigromaculatus (Hemiptera: Cicadellidae: Deltocephalinae) with phylogenetic consideration - Wenjia Yang; Yarong Gao; Can Li; Yuehua Song (Mitochondrial DNA. Part B. Resources, 2019)
The complete mitochondrial genome of the leafhopper Chlorotettix nigromaculatus was described in this study. The circular molecule is 15,011 bp in length (GenBank accession no. MK234840), consisted of 13 protein-coding genes (PCGs), 22 tRNA genes, two rRNA genes, and a putative control region. The base composition values for the mitogenome were 42.4, 13.3, 10.4, and 33.9% for A, C, G, and T, respectively. All the 22 tRNAs have the typical cloverleaf structures, except for trnS1 which lacked the dihydrouridine arm. All the 13 PCGs initiated with ATN codons and most of them terminated with TAG or TAA codons, whereas cox2, nad1, and nad4 used a single T residue. The rrnL and rrnS genes were 1220 and 745 bp in length, respectively. Phylogenetic analysis using amino acid sequences of 13 PCGs showed that C. nigromaculatus was clustered with six Deltocephalinae species, which was consistent with the conventional classification.